Sarcopenia de acordo com o EWGSOP2: como o ponto de corte da força de preensão manual afeta a prevalência e seus fatores associados? - Lima, Sara Souza (2024)
Introduction: In the updated version of EWGSOP2 to diagnose sarcopenia, muscle strength became the main and initial parameter of the assessment. However, despite the EWGSOP2 proposing handgrip strength (HGS) cutoff points to indicate muscle weakness, there is no consensus on what would be the best cutoff point, nor is it known how the use of cutoff points other than those established by the European consensus can modify the prevalence of sarcopenia and its associated factors. Objective: To compare the prevalence and factors associated with sarcopenia, having the definition of weakness established by two different cutoff points for HGS. Methods: This is a cross-sectional study with data from 7,065 participants from the ELSI-Brazil Study aged ≥ 50 years. Sarcopenia was defined by the EWGSOP2 criteria and using two cutoff points for HGS: <27 kg and <16 kg or <36 kg and <23 kg for men and women, respectively. After establishing the prevalences of probable sarcopenia, sarcopenia and severe sarcopenia using both cutoff points, two mutinomial regression models were performed to analyse which sociodemographic, behavioral and clinical factors would be associated with each of these conditions. Results: Higher cutoff points for HGS implied a higher prevalence of probable sarcopenia (40.1 versus 10.6%), sarcopenia (5.0 versus 1.4%) and severe sarcopenia (8.8 versus 3.9%). Regardless of the cutoff point used to define weakness, increasing age increased the chance of presenting all states of sarcopenia (probable sarcopenia: HGS <27/16 kg OR=1.03 CI95% 1.02-1.04 versus HGS <36/23 kg OR=1.05 CI95% 1.04-1.06; sarcopenia: HGS <27/16 kg OR=1.08 CI95% 1.05-1.10 versus HGS <36/23 kg OR=1.10 CI95% 1.08-1.12; severe sarcopenia: HGS <27/16 OR=1.13 CI95% 1.11-1.15 versus HGS <36/23 kg OR=1.17 CI95% 1.15-1.19). Sedentary lifestyle (HGS <27/16 kg OR=1.44 CI95% 1.18-1.77; HGS <36/23 kg OR=1.25 CI95% 1.07-1.47), longer duration of diabetes (HGS <27/16 kg OR=1.02 CI95% 1.01-1.04; HGS <36/23 kg OR=1.03 CI95% 1.02-1.05), spine osteoarthritis (HGS <27/16 kg OR=1.28 CI95% 1.04-1.58; HGS <36/23 kg OR=1.16 CI95% 1.01-1.33), stroke (HGS <27/16 kg OR=3.12 CI95% 2.05-4.75; HGS <36/23 kg OR=2.31 CI95% 1.55-3.43), osteoporosis (HGS <27/16 kg OR=1.41 CI95% 1.12-1.77; HGS <36/23 kg OR=1.27 CI95% 1.05-1.53) and low income (HGS <27/16 kg OR=1.49 CI95% 1.10-2.02; HGS <36/23 kg OR=1.41 CI95% 1.08-1.83) were associated with a greater chance of probable sarcopenia, regardless of the HGS cutoff point, being low income (fifth quintile: HGS <27/16 kg OR=1.95 CI95% 1.05-3.61; HGS <36/23 kg OR=1.78 CI95% 1.22-2.59) also associated with severe sarcopenia. Better memory performance reduced the chance of presenting probable sarcopenia (HGS <27/16 kg OR=0.92 CI95% 0.89-0.94; HGS <36/23 kg OR=0.93 CI95% 0.91-0.95) and severe sarcopenia (HGS <27/16 kg OR=0.86 CI95% 0.81-0.91; HGS <36/23 kg OR=0.92 CI95% 0.88-0.97), regardless of the cutoff point adopted. The risk of malnutrition and malnutrition were associated with greater odds of sarcopenia (risk of malnutrition: HGS <27/16 kg OR=2.96 CI95% 1.58-5.53; HGS <36/23 kg OR=3.31 CI95% 2.45-4.46; malnutrition: HGS <27/16 kg OR=4.96 CI95% 1.95-12.58; HGS <36/23 kg OR=6.19 CI95%3.91-9.81) and severe sarcopenia (risk of malnutrition: HGS <27/16 kg OR=1.80 CI95% 1.23-2.64; HGS <36/23 kg OR=2.45 CI95% 1.89-3.17; malnutrition: HGS <27/16 kg OR=6.45 CI95% 4.18-9.94; HGS <36/23 kg OR OR=11.23 CI95% 7.90-15.96), while being female (HGS <27/16 kg OR=0.42 CI95% 0.24-0.73; HGS <36/23 kg OR=0.53 CI95% 0.38-0.75) reduces the odds of having sarcopenia at both cutoff points. Conclusion: Adopting higher HGS cutoff points to define weakness, the prevalence of probable sarcopenia and sarcopenia quadrupled, while the prevalence of severe sarcopenia doubled. The factors associated with sarcopenia states are similar regardless of the HGS cutoff point adopted. Therefore, use higher cutoff points to identify weakness appears to be better for identifying sarcopenia, allowing the anticipation of interventions that prevent adverse health outcomes as a consequence of this disease.